Responses of phenology, yield attributes, and yield of wheat varieties under different sowing times in Indo-Gangetic Plains - Sattar, Abdus; Nanda, Gangadhar; Singh, Gulab; Jha, Ratnesh Kumar; Bal, Santanu Kumar (Frontiers in Plant Science, 2023)
A field experiment with wheat was conducted at Pusa (25.98°N, 85.67°E, 52 m amsl), Bihar (middle Gangetic plains of India) to assess the responses of phenology, yield attributes, and yield to growing season temperature and heat stress. For this purpose, wheat was planted on five dates viz. 15 November, 25 November, 5 December, 15 December, and 25 December for three consecutive years viz. 2014-15, 2015-16, and 2016-17 with three prominent cultivars of the region viz. RAU-3711, HD-2824 and HD-2733. Five dates of sowing represent different wheat-growing micro-environments as imposed by varying sowing dates encompassing the entire sowing window. The study observed the significant effect of sowing dates on phenophase duration. In general, with progress in the date of sowing, tiller initiation was delayed, while the reverse trend was observed for later growth phases. Sowing environments significantly influenced the number of effective tillers m-2. Average numbers of effective tillers (ET) m-2 for the wheat sown during 15-25 November were almost 11.6 % higher than that of the 25 December sown crop. Grain filling duration (GFD) showed a declining trend with the advancement of sowing dates due to increased thermal load on the crop during the reproductive period. 15 November planted crop exhibited the highest GFD (47 days), which was shortened significantly beyond 25 November, signifying agrometeorological non-suitability of wheat sowing beyond this window. Wheat sown on 25 November recorded the highest grain yield (3.21 Mg ha-1), 48.61 % higher than the 25 December sown crop, due to the congenial thermal regime. In this context, we have identified optimal and sub-optimal conditions to escape heat stress for higher wheat productivity. Moreover, the sum of deviation of temperature from optimum thresholds, computed for sensitive growth phases (50 % flowering to physiological maturity) helped us to identify heat stress and its impact on wheat. GGE biplot analysis revealed that RAU-3711 was found to be the most stable cultivar. A decrease in the yield of wheat by 4.9 to 12.0 %, sown during November and 33.8 to 42.4 % during December is predicted in 2050-51 and 2080-81, respectively under RCP 4.5.